2016
DOI: 10.1186/s40504-016-0034-6
|View full text |Cite
|
Sign up to set email alerts
|

Parental perspectives on consent for participation in large-scale, non-biological data repositories

Abstract: BackgroundData sharing presents several challenges to the informed consent process. Unique challenges emerge when sharing pediatric or pregnancy-related data. Here, parent preferences for sharing non-biological data are examined.MethodsGroups (n = 4 groups, 18 participants) and individual interviews (n = 19 participants) were conducted with participants from two provincial, longitudinal pregnancy cohorts (AOB and APrON). Qualitative content analysis was applied to transcripts of semi-structured interviews.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…A cross-sectional, online survey was used to assess consent preferences of parents enrolled in two Alberta birth cohorts for the secondary use of adult and child non-biological, de-identified cohort data via a non-biological data repository. This survey represents the final stage of a mixed-methods study examining parental views on privacy, consent and governance in secondary data use; the qualitative findings that preceded and informed survey development are published elsewhere [ 52 54 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cross-sectional, online survey was used to assess consent preferences of parents enrolled in two Alberta birth cohorts for the secondary use of adult and child non-biological, de-identified cohort data via a non-biological data repository. This survey represents the final stage of a mixed-methods study examining parental views on privacy, consent and governance in secondary data use; the qualitative findings that preceded and informed survey development are published elsewhere [ 52 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…The online survey was administered via the University of Alberta’s Electronic Patient Reported Outcomes (ePRO) platform. Survey design was based on previous qualitative findings, a literature review of participant and public and parent perspectives on data sharing, and pre-testing using cognitive interviewing (CI) [ 53 , 54 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Professionals working in hospices or community settings were more likely to consent to data sharing than those working in hospital. Manhas et al (2016) explored parental perspectives on paediatric RDRs for non-biological data in Canada and found that parents strongly supported the sharing of their own and their child's non-biological data, but they did express reservations relating to privacy, relationships and governance that should be considered in RDR development. The authors noted that many of the parents found the concepts of data sharing and data repositories a complex topic, meaning that a great deal of information and time was needed for participants to offer truly informed comment.…”
Section: Vie Ws Of Re S E Arch S Tudy Parti Cipantsmentioning
confidence: 99%
“…EDITORIAL circumstances may be identifiable from minimal amounts of contextual detail (Manhas et al, 2016). Current MRC guidance recommends that under these circumstances research can continue but is subject to General Data Protection Regulation (GDPR) considerations, by managing data disclosure through consent (MRC, 2019).…”
mentioning
confidence: 99%